A survey on mental health among resident physicians: psychological resilience as a mediator - Yunjuan He; Shengnan Lin; Yixuan Wang; Bo Zhang; Yifan Wang; Shouqin Sheng; Xinlong Gu; Wenyan Wang (BMC Psychiatry)
Abstract Background Sleep disturbances (SD) among resident physicians have been shown to negatively impact their mental health, potentially leading to suicidal ideation (SI) and reduced life satisfaction (LS). Psychological resilience (PR) is thought to buffer the negative effects of stressors, including SD, and may play a mediating role in this relationship. However, the specific mechanisms linking SD, PR, SI, and LS remain underexplored. This study aimed to examine the mediating role of PR in the relationship between SD, SI, and LS among resident physicians in China, building upon existing theories of resilience and stress in medical professionals. Methods An anonymous four-part survey was conducted with 453 resident physicians training in tertiary hospital in China. Descriptive statistics and correlation analyses were performed using the Statistical Package for the Social Sciences software (version 27.0). The study employed structural equation modeling(SEM) to examine the interplay of variables and conducted a multiple-group analysis using Analysis of Moment Structure (version 23.0). Results Based on a hypothetical model, SEM revealed that PR played a partial mediating role in the relationship between SD and SI (52.10% of the total effect of SD on SI was direct, and 47.90% of the total effect was mediated by PR). Moreover, in the relationship between SD and LS, PR also acted as a partial mediator, accounting for 79.00% of the direct effect of SD on LS and 21.00% of the effect mediated by PR. The multiple-group analysis further revealed that individuals over 25 years exercise more PR to enhance LS (t = 2.703, p < 0.01), and those with normal weight were less affected by SD in terms of LS (t = − 2.322, p = 0.02). Conclusions PR serves as a significant mediator in the relationship between SD and both SI and LS. These findings highlight the importance of fostering PR in resident physicians to mitigate the adverse effects of SD on their mental health and well-being. Policymakers and medical institutions should prioritize interventions aimed at improving sleep quality and supporting mental health to enhance the overall well-being of resident physicians.